1998
DOI: 10.1073/pnas.95.13.7327
|View full text |Cite
|
Sign up to set email alerts
|

Effective inhibition of influenza virus production in cultured cells by external guide sequences and ribonuclease P

Abstract: The polymerase (PB2) and nucleocapsid (NP) genes encoded by the genome of inf luenza virus are essential for replication of the virus. When synthetic genes that express RNAs for external guide sequences targeted to the mRNAs of the PB2 and NP genes are stably incorporated into mouse cells in tissue culture, infection of these cells with inf luenza virus is nonproductive. Endogenous RNase P cleaves the targeted inf luenza virus mRNAs when they are in a complex with the external guide sequences. Targeting two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 44 publications
2
79
0
Order By: Relevance
“…Antisense technology has been shown to be a promising gene targeting approach for use in basic research and clinical therapeutic applications+ The gene-targeting agents used can be a conventional antisense oligonucleotide, an antisense catalytic molecule (ribozyme or DNA enzyme), or an antisense molecule with an additional (guide) sequence that targets the mRNA for degradation by endogenous RNases such as RNase L and RNase P (Stein & Cheng, 1993;Maran et al+, 1994;Poeschla & Wong-Staal, 1994;Yuan & Altman, 1994;Rossi, 1995;Santoro & Joyce, 1997;Plehn-Dujowich & Altman, 1998)+ Antisense molecules with guide sequences have several unique features as gene targeting agents+ It has been shown that targeting of mRNAs with these molecules for degradation by RNase P and RNase L results in irreversible cleavage and the cleavage can be in a catalytic fashion (Yuan et al+, 1992;Maran et al+, 1994;Yuan & Altman, 1994)+ Moreover, this targeting approach uses the cellular endogenous RNases for degradation of the target mRNA and, therefore, assures the stability and efficiency of the targeting enzymes in the cellular environment+ Ribonuclease P (RNase P) has been found in all organisms examined and is one of the most abundant, stable, and efficient enzymes in cells (Altman et al+, 1993;Pace & Brown, 1995)+ Its enzymatic activity is responsible for the maturation of 59 termini of all tRNAs which account for about 2% of total cellular RNA (Gopalan et al+, 1995)+ This enzyme is a ribonucleoprotein complex and catalyzes a hydrolysis reaction to remove the leader sequence of precursor tRNA (Altman et al+, 1993;Pace & Brown, 1995)+ RNase P from Escherichia coli has been extensively studied+ It contains a catalytic RNA subunit of 377 nt termed M1 RNA and a single polypeptide of 119 amino acids known as C5 protein (Altman et al+, 1993;Pace & Brown, 1995)+ In the presence of a high concentration of Mg 2ϩ , M1 RNA itself can hydrolyze tRNA precursors in vitro (Guerrier-Takada et al+, 1983)+ However, the addition of C5 protein dramatically increases the rate of cleavage in vitro and is required for cleavage in vivo (Guerrier-Takada et al+, 1983)+ Human RNase P also contains an RNA subunit, H1 RNA, 344 nt in length (Bartkiewicz et al+, 1989)+ However, in the absence of protein factors, H1 RNA does not exhibit enzymatic activity by itself in vitro …”
Section: Introductionmentioning
confidence: 99%
“…Antisense technology has been shown to be a promising gene targeting approach for use in basic research and clinical therapeutic applications+ The gene-targeting agents used can be a conventional antisense oligonucleotide, an antisense catalytic molecule (ribozyme or DNA enzyme), or an antisense molecule with an additional (guide) sequence that targets the mRNA for degradation by endogenous RNases such as RNase L and RNase P (Stein & Cheng, 1993;Maran et al+, 1994;Poeschla & Wong-Staal, 1994;Yuan & Altman, 1994;Rossi, 1995;Santoro & Joyce, 1997;Plehn-Dujowich & Altman, 1998)+ Antisense molecules with guide sequences have several unique features as gene targeting agents+ It has been shown that targeting of mRNAs with these molecules for degradation by RNase P and RNase L results in irreversible cleavage and the cleavage can be in a catalytic fashion (Yuan et al+, 1992;Maran et al+, 1994;Yuan & Altman, 1994)+ Moreover, this targeting approach uses the cellular endogenous RNases for degradation of the target mRNA and, therefore, assures the stability and efficiency of the targeting enzymes in the cellular environment+ Ribonuclease P (RNase P) has been found in all organisms examined and is one of the most abundant, stable, and efficient enzymes in cells (Altman et al+, 1993;Pace & Brown, 1995)+ Its enzymatic activity is responsible for the maturation of 59 termini of all tRNAs which account for about 2% of total cellular RNA (Gopalan et al+, 1995)+ This enzyme is a ribonucleoprotein complex and catalyzes a hydrolysis reaction to remove the leader sequence of precursor tRNA (Altman et al+, 1993;Pace & Brown, 1995)+ RNase P from Escherichia coli has been extensively studied+ It contains a catalytic RNA subunit of 377 nt termed M1 RNA and a single polypeptide of 119 amino acids known as C5 protein (Altman et al+, 1993;Pace & Brown, 1995)+ In the presence of a high concentration of Mg 2ϩ , M1 RNA itself can hydrolyze tRNA precursors in vitro (Guerrier-Takada et al+, 1983)+ However, the addition of C5 protein dramatically increases the rate of cleavage in vitro and is required for cleavage in vivo (Guerrier-Takada et al+, 1983)+ Human RNase P also contains an RNA subunit, H1 RNA, 344 nt in length (Bartkiewicz et al+, 1989)+ However, in the absence of protein factors, H1 RNA does not exhibit enzymatic activity by itself in vitro …”
Section: Introductionmentioning
confidence: 99%
“…The expression of these EGSs in human cells led to inhibition of the expression of the target genes and blockage of viral replication. This study further provided the direct evidence that targeting two different mRNAs simultaneously by the EGS technology inhibits viral growth more effectively than targeting of one mRNA only [74].…”
Section: Antiviral Agentsmentioning
confidence: 76%
“…Recent studies in our laboratory and others have shown that using EGS to recruit endogenous RNase P for targeted degradation of viral mRNA is highly effective. For example, Altman and colleagues constructed EGSs that targeted the mRNAs coding for the polymerase and nucleocapsid protein of human influenza virus, which are essential for viral replication [74]. The EGS RNAs are efficient in inducing RNase P to cleave the target viral mRNAs in vitro.…”
Section: Antiviral Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…External guide sequence technique, a novel approach, can specifically cleave target molecular by RNase P. Previous studies have demonstrated that RNA inactivation of targeted mRNA by EGS in vivo can be more effective than gene inactivation by conventional antisense DNA oligonucleotides [13,14], which have a different gene inactivation mechanism by endogenous RNase H [15,16]. Reduced off-site cleavage by EGS is also an advantage of EGS relative to RNAi and antisense technologies [17,18].…”
Section: Discussionmentioning
confidence: 99%